An Automatic System for Continuous Monitoring and Sampling of Groundwater Geochemistry in Earthquake-Prone Regions of SW Taiwan - Fu, Ching-Chou; Lai, Chun-Wei; Yang, Tsanyao Frank; Hilton, David R.; Chen, Cheng-Hong; Walia, Vivek; Kumar, Arvind; Lee, Lou-Chuang (Frontiers in Earth Science, 2021)
Previous studies have revealed that gas compositions of fluid samples collected from southwestern Taiwan, where many hot springs and mud volcanoes are distributed along with tectonic structures, show significant variation before and after some disaster seismic events. Such variations, including radon activity, CH4/CO2, and 3He/4He ratios of gas compositions, are considered precursors of earthquakes in this area. An automatic system for continuous on-line gas monitoring and groundwater sampling was established at Yun-Shui (YS), where an artesian well located at an active fault zone in SW Taiwan, to validate the relationship between fluid compositions and seismicity. It is equipped with a quadrupole mass spectrometer (QMS) and a radon detector for in-situ measurement of the dissolved gas composition. Variations of dissolved gas compositions are transmitted to the laboratory through the internet. Furthermore, a syringe pump apparatus for the retrieval and temporal analysis of helium (SPARTAH) is also installed for off-line laboratory analysis for obtaining the detailed time-series records of helium, hydrogen, oxygen, and dissolved inorganic carbon (DIC) isotopic compositions as well as dissolved inorganic carbon and chloride concentration of water samples at this station. After continuous monitoring for several months, two substantial anomalies of multiparameter were observed prior to the significant earthquakes. This automated system has been demonstrated to be feasible for long-term continuous seismo-geochemical research in this area.